Performa dan Hasil Padi Beras Hitam Beliah terhadap Pemupukan Di Lahan Sawah Pasang Surut - Panturi, Sebastian Reni; Darussalam, Panturi Astina (Jurnal Sains Pertanian Equator, 2020)
Rice (Oryza sativa L.) is one of the main food sources in Indonesia. Beliah black rice from Bengkayang is one of the local rice that is popular in the community. The purpose of this study was to study the performance of Beliah black rice in swam paddy fields to and study how the yield of Beliah black rice which were given fertilizer and were not given fertilizer. The study was conducted in the Solo Trench, Sungai Kakap District, Kubu Raya Regency. The research period was 8 months starting from March until November 2019. This research uses a field research method with a total sample of 60 plant samples. The treatment consists of no fertilizer, ½ recommended doses and full fertilizer doses. The recommended dosage of fertilizer used were Urea 150 kg / ha (3.24 kg / plot), SP-36 135 kg / ha (2.9 kg / plot), and KCl 100 kg / ha (2.16 kg / plot). The variables observed were total number of tiller, number of productive tiller , plant height, flowering time, panicle length, panicle exert, seed length, seed width , number of grains per panicle, fertility of grain, plant age, weight of 1000 grains, and grains contents per clump. The data obtained by the mean calculation based on the Guide to Characterization and Evaluation System of Rice Crops (Ministry of Agriculture, 2003) and then observing variables that have different characters are carried out Simple Linear Regression Test and Paired Sample t-Test to see how much the fertilizer response. The yield of the study showed that the total number of tillers, number of productive tillers, plant height, first headings, main headings, plant age, and weight of 1000 grains gave fertilizer responses but did not respond to other parameters. Fertilizer treatment, according to recommended doses (150 Urea kg / ha, 135 SP-36 kg / ha, 100 KCl kg / ha) gives the highest yield of filled grain weight which was 18,90 g/clump.